Investigating 21st Century Skills Level among Youth: An Empirical Study - Varghese, Jijo; M.N Mohamedunni Alias Musthafa (GILE Journal of Skills Development, 2021)
Twenty-first century skills are a set of capabilities and competencies that students need to cultivate and develop to succeed in the age of information and technology. The success and growth of today's youth in the labour market and the knowledge economy depend on the level of 21st century skills they possess. Hence the key objective of this study was to answer the questions: to what extent do the youth possess 21st century skills? Is there a difference between levels of 21st century skills on account of various demographic variables? The researchers used the descriptive survey method and selected 160 college students randomly from various higher education institutions of Kerala, the southern part of India, for the study. The significant findings of this study revealed that 15.6% have a Low level, 68.1% have an Average level, 16.3% have a high level of 21st-century skills. No significant difference exists between males and females and stream of subjects of college students with respect to the level of 21st century skills, but there is a substantial difference between the youth who belong to the urban and rural locality.